Assessment of brittle fracture for PUR materials using local strain energy density and theory of critical distances. (October 2015) - Negru, R.; Marsavina, L.; Filipescu, H.; Căplescu, C.; Voiconi, T.
Highlights: Local SED and TCD methods were applied to predict maximum fracture load. SENB U-notched and ASCB cracked specimens were investigated. PUR materials of two densities were considered. Both methods provide reasonable predictions for the fracture load. Abstract: Local strain energy density and theory of critical distances represent two recent approaches in assessing the brittle fracture of cracked and notched components. Experimental validation of these methods was mainly conducted on materials with brittle behaviour (ceramics and PMMA). In this paper the applicability of these methods to another class of plastic materials, i.e. rigid polyurethanes of different densities, was investigated. For this, two types of specimens, single edge U-notched and asymmetric semi-circular bend cracked specimens, were experimentally investigated at room temperature and considered for theoretical predictions. Both criteria provide reasonable predictions for the fracture load.